2014
DOI: 10.1007/s10964-014-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations Between Adolescent and Parental Behaviors, Parental Knowledge, and Internalizing Behaviors Among Urban Adolescents

Abstract: High prevalence rates of depression and anxiety among adolescents underscore the importance of identifying parental and adolescent behaviors that may lessen the risk for these outcomes. Previous research has shown that parental acceptance, parental knowledge, and child disclosure are negatively associated with internalizing behaviors. It is also important to explore the impact of internalizing behaviors on these parental and child constructs. The current study examined longitudinal relationships between parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 67 publications
3
35
1
1
Order By: Relevance
“…This difference may have emerged because our earlier study combined parent perceptions of child internalizing behavior and actual child experiences of internalizing behavior in one measure (by averaging mother, father, and child reports). However, parent perceptions of child internalizing behaviors might be less accurate as children age into adolescence, spend more time outside the home, and share less about their internal states (Garthe et al, ). Thus, child effects on parenting may be less prevalent in adolescence in studies (like ours) that primarily capture child self‐reported internalizing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may have emerged because our earlier study combined parent perceptions of child internalizing behavior and actual child experiences of internalizing behavior in one measure (by averaging mother, father, and child reports). However, parent perceptions of child internalizing behaviors might be less accurate as children age into adolescence, spend more time outside the home, and share less about their internal states (Garthe et al, ). Thus, child effects on parenting may be less prevalent in adolescence in studies (like ours) that primarily capture child self‐reported internalizing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…warmth, acceptance, support, involvement) as well as parent-child relationships (e.g. openness, closeness, warmth) have been touted as powerful tools to promote a positive socio-emotional, behavioural, and academic development (Garthe, Sullivan, & Kliewer, 2015;Ginevra et al, 2015;Shumow & Lomax, 2002;Surjadi, Lorenz, Wickrama, & Conger, 2011;Wang, Hill, & Hofkens, 2014;Wang & Sheikh-Khalil, 2014;Wilder, 2014). Nevertheless, among several parenting practices, parental involvement in school education is one that is most important regarding educational outcomes and future success (Bempechat & Shernoff, 2012;Gordon & Cui, 2012;LaRocque, Kleiman, & Darling, 2011;Wang & Sheikh-Khalil, 2014;Wilder, 2014).…”
mentioning
confidence: 99%
“…Estos resultados se encuentran consistentemente en todas las investigaciones que han tratado este temática, la crianza positiva produce efectos beneficiosos sobre los hijos mientras que la crianza negativa correlaciona con la aparición de diversas problemáticas en los hijos (Carrasco y Rohner, 2013;Carrasco et al, 2009;Garthe, sullivan y Kliewer, 2014; Mesurado y Minzi, 2013; Rudolph y Zimmer-Gembeck, 2014).…”
Section: Discussionunclassified